Polycyclic aromatic hydrocarbons in Iranian Kebabs. (February 2016) - Gorji, Mohamad Es'haghi; Ahmadkhaniha, Reza; Moazzen, Mojtaba; Yunesian, Masud; Azari, Ali; Rastkari, Noushin
Abstract: The presence and amount of 15 polycyclic aromatic hydrocarbons (PAHs) were determined in four types of commonly consumed well-done grilled meat (Kebab) in Tehran restaurants. The main goal was to assess the hazard potential of grilled meat prepared in Tehran restaurants and to determine the contributions of fuel and meat types on concentrations of PAHs in Kebabs. Based on the results, the total PAHs concentration was in the range from 7.37 to 17.94 μg kg −1 . The differences in PAHs concentrations were found to be significant between charcoal and gas-grilled samples as well as between different meat types. The highest and lowest concentrations of PAHs were detected in charcoal grilled chicken wings and gas grilled chicken meat respectively. Benzo[a]pyrene (BaP), one of the main indicators for the occurrence of PAHs in food, was detected in all the samples in the range of 0.28–5.81 μg kg −1 . In addition, four samples exceeded the maximum acceptable limit for BaP established by the European Commission. Highlights: 15 polycyclic aromatic hydrocarbons were determined in four types of grilled meat. The effects of different factors on PAHs content of grilled meat were discussed. Compared to gas grilling, charcoal grilling led to higher PAHs contents in kebabs. The highest PAHs content was detected in charcoal grilled chicken wings samples. There were significant differences in PAHs concentrations between beef & chicken.